Polityczna przydatność nierówności etnicznych – nacjonalizm w prozie Dubravki Ugrešić - Biernacki, Tomasz (2022)
The outbreak of the civil war in Yugoslavia was the end of a certain stage in Dubravka Ugrešic’s writing. The shockexperienced by the novelist and essayist in the first half of the 90s radically changed the nature of her literary work.One of the leading themes was that of Croatian and Serbian nationalism producing inequality, which was presentedas a politically useful construct. The article focuses on three collections of essays by Dubravka Ugrešic: The culture oflies (1996), Nobody’s Home (2005) and Fox (2017). The article presents a detailed discussion of the author’s attitudto the wartime and post-war reality, which focused on dividing communities that had coexisted for decades inrelative agreement. The pessimistic overtone of these ironic essays leaves no illusions as to the nature of nationalismas a dangerous tool in the hands of those who exercise power or wish to gain it by creating ethnic inequalities.
Keywords: Yugoslavia; nationalism; trauma; ethnic inequalities